Elected Women Panchayat Samiti: An Structural Arrangement for Farm Women Empowerment in India - Anuradha Ranjan Kumari , S. K. Dubey and US Gautam, (Indian Journal of Extension Education, 2016)
Women represent almost half of the human resources and half the potential in all the societies. India being no exception toit and, therefore, the employment and autonomy of women and level of women's social achievement are the indicators ofsustainable development. Empowerment is a process, not an event, which challenges traditional power equations andrelations. Abolition of gender-based discrimination in all institutions and structures of the society and participation ofwomen in policy and decision making process at domestic and public levels are few dimensions of women empowerment.The present study was an effort to know the extent of empowerment and associated problem of elected women members inPanchayati Raj institutions. Total Twenty Three women representatives were randomly sampled from Pusa andKalyanpur block of Samastipur district in Bihar province in Indiafrom the 40 randomly drawn villages from the twoselected blocks of the above districts. The tool used for collecting information was pre-structured interview schedule anddata were collected through personal interview method. In order to determine the conditions sowing the empowerment ofwomen the data were subjected to correlation and multiple regressions analysis. Their extent of empowerment was takenas dependent variables. The finding revealed that 21.73 percent of the respondents were highly empowered with respect to“Health welfare and Development of Public Property.The association between empowerment and farm womens' age wasnegative but highly significantly associated (P